2008
DOI: 10.3989/scimar.2008.72n4743
|View full text |Cite
|
Sign up to set email alerts
|

Primera liberación de juveniles de mero <i>Epinephelus marginatus</i> (Lowe, 1834) (Serranidae: Teleostei) cultivados en criadero en arrecifes artificiales en el mar Mediterráneo: resultados de un estudio experimental

Abstract: SUMMARY: A pilot experiment of stock enhancement based on the release of hatchery-reared juveniles of dusky grouper, Epinephelus marginatus, was carried out at two artificial reefs located 0.9 km offshore the south-western Sicilian coast (Central Mediterranean). The fish assemblages inhabiting the reefs were characterized using underwater visual census (UVC) surveys. Despite some differences in fish species richness, diversity and abundance, both artificial reefs provide suitable feeding resources and shelter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Provision of food [59,60], spawning [61] and shelter opportunities [62] by artificial structures are among the main themes dominating the literature, causing changes in fish abundance, biodiversity and distribution. In general, the vast majority of the AR studies (94%) reported that fish abundance and biodiversity increased or was unaffected by AR deployment.…”
Section: Effects Of Ars and Owfs On Fish Abundancementioning
confidence: 99%
“…Provision of food [59,60], spawning [61] and shelter opportunities [62] by artificial structures are among the main themes dominating the literature, causing changes in fish abundance, biodiversity and distribution. In general, the vast majority of the AR studies (94%) reported that fish abundance and biodiversity increased or was unaffected by AR deployment.…”
Section: Effects Of Ars and Owfs On Fish Abundancementioning
confidence: 99%
“…Una alternativa ha sido la acuicultura, por ello ha crecido rápidamente al convertirse en el sector de mayor aumento en producción animal, además de complementar la producción pesquera para consumo humano, podría ayudar a su restauración, por medio de la liberación de especies producidas en cautiverio (Naylor et al, 2000;Ayer y Teyedmers, 2008). La liberación de especies acuícolas es una actividad cada vez más frecuente y promisoria en la conservación de muchas especies, tanto de aguas continentales (Lopera-Barrero et al, 2009;Torregroza-Espinosa et al, 2015), como marinas (Bell et al, 2006;Valencia et al, 2007;Sparrevohn y Støttrup, 2008;Bell et al, 2008;La Mesa et al, 2008;Obolski et al, 2016).…”
Section: Introductionunclassified